Discussion of “The implications of unverifiable fair-value accounting: Evidence from the political economy of goodwill accounting” - Skinner, Douglas J. (Journal of Accounting and Economics, 2008)
Ramanna [2007. The implications of unverifiable fair-value accounting: evidence from the political economy of goodwill accounting, Journal of Accounting and Economics] provides interesting and novel evidence on how firms use contributions from their political action committees (PACs) to members of Congress as a means of lobbying for preferred positions on the two exposure drafts that led to SFAS-141 and SFAS-142. My discussion raises some concerns about his main conclusion: that pooling firms lobbied the FASB to obtain a “fair-value”-based impairment rule to facilitate their ability to manipulate financial statements. I offer a more benign explanation and make some other observations about how this line of research could proceed in the future.